The strict typology : theory, generalizations and applications - Diss, Gordon Fletcher (Department of Mathematics and Applied Mathematics, 2015)
The strict topology β was first defined on the space of bounded complex-valued continuous functions Cb(X), on a locally compact Hausdorff space X, by Buck. It was found to have many applications in Approximation Theory, spectral synthesis, spaces of bounded holomorphic functions and multipliers of Banach Algebras.